Relationship between Lithology Factor and Landslide Occurrence based on Information Value (IV) and Frequency Ratio (FR) Approaches- Case Study in North of Iran. - Omar, Husaini; Kim Huat, Bujang; Md Yusoff, Zainuddin; Safaei, Mehrdad (2012)
This study was conducted on the Land sliding areas in the southern part of the city of Sari. Due to the important role of Lithology in the study area, an attempt was made to determine the potential land sliding areas. Consequently, a digital mapping and of the location of these Landslides in the region were performed. Then, using statistical methods, density, frequency and information value of the types of geology formation in the study areas were evaluated. As a result, it became clear that the Paleocene and Plio-Miocene formations were the most important formations of land sliding and as compared to other litho types; they possess the highest marl contents which are of unstable nature. These rock types constituted a major part of foundation of these villages in the areas.